Gleichstellungspolitik öffentlicher Arbeitgeber Betriebliche Gleichstellung in den Bundesverwaltungen Deutschlands, Österreichs und der Schweiz - Fuchs, Gesine (Verlag Barbara Budrich, 2016)
There are many political measures for equality in the profession, but why do they still lack the resounding success? What dynamics are at work in the implementation and enforcement of these measures, and how can equality policies be better designed and coordinated in the future? In order to find answers to these questions, the authors compare the structures and measures of corporate equality policies of public employers using the example of federal administrations in Switzerland, Germany and Austria.